2018
DOI: 10.1155/2018/4021952
|View full text |Cite
|
Sign up to set email alerts
|

Could the Combined Administration of Bone Antiresorptive Drug, Taxanes, and Corticosteroids Worsen Medication Related Osteonecrosis of the Jaws in Cancer Patients?

Abstract: The study presents a report of 58 metastatic cancer patients who developed osteonecrosis of the jaws after being treated with zoledronic acid and taxanes, plus corticosteroids. A retrospective analysis of data registered in the archives of two Italian osteonecrosis of the jaws treatment centers, who are based at the University of Messina and at the University of Palermo, was performed in order to study, in these patients, demographic data and characteristics such as frequency of cancer location, lines of thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Bi et al [ 21 ] reported that chemotherapeutic agents resulted in larger sequestrum and soft tissue defects in the mouse MRONJ model. Oteri et al [ 16 ] hypothesized that the concurrent administration of chemotherapeutic agents could worsen the clinical manifestation of MRONJ. On the basis of that, we designed a case-control study and demonstrated that combined administration of bisphosphonates and chemotherapeutic agents could increase the risk for stage 3 MRONJ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bi et al [ 21 ] reported that chemotherapeutic agents resulted in larger sequestrum and soft tissue defects in the mouse MRONJ model. Oteri et al [ 16 ] hypothesized that the concurrent administration of chemotherapeutic agents could worsen the clinical manifestation of MRONJ. On the basis of that, we designed a case-control study and demonstrated that combined administration of bisphosphonates and chemotherapeutic agents could increase the risk for stage 3 MRONJ.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known regarding whether those agents are the risk indicators of stage 3 MRONJ. Oteri et al [ 16 ] reported that chemotherapy could worsen the clinical manifestation of MRONJ. Nevertheless, the conclusion was limited due to the absence of data from a case and control study and insufficient statistical evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Although comorbid conditions under effective control were not a risk factor predisposing for the development of MRONJ, the prevalence of comorbid conditions in MRONJ patients was evaluated in view of the average age of the cohort, and the results confirmed the increasing prevalence of multimorbidity among older adults [ 12 ]. The increasing awareness of the risk for MRONJ among patients assuming novel molecules for cancer treatment [ 13 ] and/or multiple medications with synergy effect has already been described [ 14 , 15 ]. It has been reported that the combination of bisphosphonates and antiangiogenic factors may increase the risk of MRONJ [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Medication-related osteonecrosis of the jaw (MRONJ) from chronic steroids and pomalidomide use was a diagnostic consideration for our second case. Non-infectious osteonecrosis has been associated with the use of several chronic medications, including intravenous high potency bisphosphonates, denosumab [ 17 ], corticosteroids [ 18 ], and combination of corticosteroids with taxanes and denosumab [ 19 ]. The possible association between actinomycotic osteomyelitis and MRONJ has been previously described and this could also have played a role in the development of osteomyelitis in our second patient [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%